Parallel computing using the prefix problem - Lakshmivarahan, S. (Oxford University Press, 1994)
This is an introduction to those aspects of parallel programming and parallel algorithms that relate to a single topic: the prefix problem. This approach provides intense development of a single computational tool used in many parallel computations, showing and discussing its techniques. The text may be used for graduate courses.